Identification of Rab41/6d Effectors Provides an Explanation for the Differential Effects of Rab41/6d and Rab6a/a' on Golgi Organization - Liu, Shijie; Majeed, Waqar; Kudlyk, Tetyana; Lupashin, Vladimir; Storrie, Brian (Frontiers in Cell and Developmental Biology, 2016)
Unexpectedly, members of the Rab VI subfamily exhibit considerable variation in their effects on Golgi organization and trafficking. By fluorescence microscopy, neither depletion nor overexpression of the GDP-locked form of Rab6a/a’, the first trans Golgi-associated Rab protein discovered, affects Golgi ribbon organization while, on the other hand, both Rab41/6d depletion and overexpression of GDP-locked form cause Golgi fragmentation into a cluster of punctate elements, suggesting that Rab41/6d has an active role in maintenance of Golgi ribbon organization. To establish a molecular basis for these differences, we screened for Rab41/6d interacting proteins by yeast two-hybrid assay. 155 non-repetitive hits were isolated and sequenced, and after searching in NCBI database, 102 different proteins and protein fragments were identified. None of these hits overlapped with any published Rab6a/a’ effector. Eight putative Rab41 interactors involved in membrane trafficking were found. Significantly, these exhibited a preferential interaction with GTP- versus GDP-locked Rab41/6d. Of the 8 hits, the dynactin 6, syntaxin 8 and Kif18A plasmids were the only ones expressing the full-length protein. Hence, these 3 proteins were selected for further study. We found that depletion of dynactin 6 or syntaxin 8, but not Kif18A, resulted in a fragmented Golgi apparatus that displayed a Rab41/6d knockdown phenotype, i.e., the Golgi apparatus was disrupted into a cluster of punctate Golgi elements. Co-immunoprecipation experiments verified that the interaction of dynactin 6 and syntaxin 8 with GTP-locked Rab41/6d was stronger than that with wild type Rab41/6d and least with the GDP-locked form. In contrast, co-immunoprecipitation interaction with Rab6a was greatest with the GDP-locked Rab6a, suggestive of a non-physiological interaction. In conclusion, we suggest that dynactin 6, a subunit of dynactin complex, the minus-end-directed, dynein motor, provides a sufficient molecular basis to explain the active role of Rab41/6d in maintaining Golgi ribbon organization while syntaxin 8 contributes more indirectly to Golgi positioning.